Effects of computer-aided clinical decision support systems in improving antibiotic prescribing by primary care providers: a systematic review. (14th August 2014) - Holstiege, Jakob; Mathes, Tim; Pieper, Dawid
Abstract: Objective To assess the effectiveness of computer-aided clinical decision support systems (CDSS) in improving antibiotic prescribing in primary care. Methods A literature search utilizing Medline (via PubMed) and Embase (via Embase) was conducted up to November 2013. Randomized controlled trials (RCTs) and cluster randomized trials (CRTs) that evaluated the effects of CDSS aiming at improving antibiotic prescribing practice in an ambulatory primary care setting were included for review. Two investigators independently extracted data about study design and quality, participant characteristics, interventions, and outcomes. Results Seven studies (4 CRTs, 3 RCTs) met our inclusion criteria. All studies were performed in the USA. Proportions of eligible patient visits that triggered CDSS use varied substantially between intervention arms of studies (range 2.8–62.8%). Five out of seven trials showed marginal to moderate statistically significant effects of CDSS in improving antibiotic prescribing behavior. CDSS that automatically provided decision support were more likely to improve prescribing practice in contrast to systems that had to be actively initiated by healthcare providers. Conclusions CDSS show promising effectiveness in improving antibiotic prescribing behavior in primary care. Magnitude of effects compared to no intervention, appeared to be similar to other moderately effective single interventions directed at primary care providers. Additional research is warranted to determine CDSS characteristics crucial to triggering high adoption by providers as a perquisite of clinically relevant improvement of antibiotic prescribing.